Estrus synchronization in swine: trials with Aimax (I.C.I. 33,838) - G Kiracofe; B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1968)
Several methods of synchronizing estrus have been tried in swine. One of the oldest and most commonly used natural methods is weaning pigs from a group of sows simultaneously. When this is done, the majority of sows will show estrus 3 to 7 days later if the sows have been nursed for at least 3 weeks. This method is effective and highly fertile; however, in some cases it is not practical to breed at this time and a natural method of synchronization in gilts is not available.; Swine Day, Manhattan, KS, September 26, 1968
Keywords: Swine day; 1968; Swine; Estrus synchronization; Sows